Seed Priming with Potassium Nitrate Impacts on Germination and Physiological Performance in Carrot - , Eshita Kundu; , Sanjoy Kumar Bordolui (Archives of Current Research International, 2025)
Introduction: In order to energize the seeds, accelerate the germination process and lessen environmental stress, a range of physiological and non-physiological treatments are available. Seed priming is one of these. It's an inexpensive, effective hydration technique that speeds up germination by increasing the pre-germinative metabolic process through controlled drying and hydration. Aims: The main aim was to evaluate effect of halo-priming with KNO3 on germination and vigour of seed. Materials and Methods: In the present study, which was conducted with three carrot genotypes and varying halo-priming concentrations and durations were employed. A completely randomized design with three replications was used. Three genotypes were Carrot Florence (G1), Deb Kuroda-1 (G2) and Deb Kuroda-3 (G3) with various concentrations and duration of KNO3 for halo priming viz. 2% for 24 H (T2), 2% for 18 H (T3), 3% for 24 H (T4), 3% for 18 H (T5), 4% for 24 H (T6), 4% for 18 H (T7) and non-primed seeds (T1). The different seed quality parameters such as time to 50% germination, mean germination time (MGT), germination index, germination Energy (%), root length, shoot length, fresh weight, dry weight, germination percentage and vigor index were recorded. Results and Discussion: Seed priming is a practical and affordable way to guarantee consistent seed development in field crops. It improves germination, vigour, nutrient uptake, water use efficiency, and the release of photo- and thermo-dormancy. Conclusion: Deb Kuroda-3 was the best genotype over all treatments. Consequently, 3% KNO3 pre-sowing treatment for 24 H is advised for carrot seed in order to improve seedling establishment and vigour.